Estudo comparativo dos intervalos de tempo para medição de velocidade crítica de peixes: estudo de caso com o "Pimelodus maculatus" - Mila Correa Sampaio (2013)
This paper presents a study of the interference of temporal factors on the results of the testing of swimming performance of fish. For this study we developed a varying time increments used for testing of swimming performance. After identifying the impact of time increments trials chose the smallest time allowing the tests and did not present statistically significant differences with time usually used in the literature (10 minutes). Then, using this time chosen, made a comparison between the results of tests performed with freshly caught fish and fish that were confined in a laboratory environment for one year (twelve months). The results indicated that it is possible to perform tests on neotropical fish with time increments of 5 minutes. It was also observed that the fish caged for a year in a lab environment showed greater swimming ability than were captured and immediately tested. At the end of the study, the opposite results, made an assessment of the ability of the species studied (Pimelodus maculatus - mandi amarelo) can enter the pipe in a hydroelectric turbine used as a case study.